Mecanismos neurales en el control del dormir - Ocampo-Garcés, Adrián; Castro F., Javiera; Espinoza C., Danay (Revista Hospital Clínico Universidad de Chile, 2012)
Neural mechanisms involved in sleep and wakefulness generation are widely distributed in the central nervous system. Current models emphasize the pivotal role of the hypothalamus in controlling the activation and inhibition of the ascending activating system and thlamo-cortical networks during wakefulness and restorative sleep respectively. The restorative properties of sleep, the duration and the timing of sleep occurrence is determined by at least two families of processes; (i) circadian rhythms generated at the hypothalamic pacemaker, that favors sleep and wakefulness at determined phases of the day; and (ii) homeostatic mechanisms that maintain the adequate daily sleep quotas, by compensating sleep debts and excesses. It is a current focus of clinical and basic research the effect of transient or chronic disruption of sleep architecture on performance and wellbeing.